Influence of quality on employee results: the case of rural accommodations in Spain - Rama, M. C. R.; García, J. A.; Saraiva, M.; Pires, A. R. (Total Quality Management and Business Excellence, 2017)
Few studies have analysed the effect of the critical factors of quality results on employees in the services sector and, more specifically, in the tourism sector. This work studies the rural accommodation sector in order to provide facility managers with the critical factors on which to focus their efforts towards increasing their employees’ job satisfaction. The data obtained from 100 rural accommodations in Spain are analysed and each of the measurement scales used are validated by exploratory and confirmatory factor analysis. The theoretical model proposed to analyse the relationship is estimated by applying Structural Equation Modelling (SEM). The research reveals that the factors to which greater attention should be paid in order to enhance employee results are quality policy and strategy and processes management, the latter being the criterion through which the rest of the critical factors perform. The greatest total effect derives from quality policy and strategy and leadership, indirect effect via the rest of the criteria.